Contemporary Social Transformations and Life Skills: Interconnections in Search of Quality of Life, Health, and Well-being (Global Journal of Human-Social Science, 2025)
In the twentieth and early twenty-first centuries, constant scientific and technological advances have brought about a number of improvements in the material conditions of existence and an immense transformation of social relations, but with many harmful effects. For this reason, we need to consider the role and importance of spiritual aspects, which go far beyond the material aspects of existence, for health, well-being and quality of life. In this sense, this research aimed to understand how the life skills proposed by the WHO can contribute to reducing the harmful effects on health and well-being of contemporary social transformations and increase quality of life. The general objective was to verify the statistical consistency of the CEVS inventory created with the aim of understanding the relationship between life skills and components of quality of life and emotional awareness. This was an action research project which aimed not only to understand the dynamics of the problem, but also to develop possible interventions to alleviate and/or resolve it. The research was submitted to the ethics committee and approved, after meeting all the requirements.
Keywords: life skills; integral health; well-being; quality of life; action research; AMAN